(untitled) (Journal of Educational Sciences, 2017)
The current paper examines Kazakhstani school teachers’ attitudes towards inclusive education and their concerns in relation to inclusion of children with special educational needs in mainstream classes/schools. The outcomes of the present study have indicated that teachers’ attitudes towards inclusion of children experiencing learning difficulties depend on the nature of those difficulties. With regard to the inclusion of students with special needs into general education, the lack of school resources is a major concern of Kazakhstani teachers, while educators are comparatively less concerned about a possible increase in their workload. The correlational analysis in several variables has suggested that the greater involvement of secondary school teachers in the implementation of inclusive education programs would help to reduce their level of concern. Key words: inclusive education, children with special needs, teacher preparation, teachers’ concerns.